Informality and its relationship with tax collection. Studies in the context of Ecuador (Dissertare, 2020)
Tax revenues are an essential part of financing the general state budget in Ecuador, therefore, it is essential to analyze the variables that affect tax collection in the country. In this sense, informality, as a phenomenon associated with tax evasion, with a marked presence in the Ecuadorian economy, has originated an important investigative production related to taxation. The objective of this work is to carry out a literature review on the study of the informal economy in Ecuador and its relationship with tax collection, including aspects related to characteristics, causes and consequences of this type of activities, as well as strategies to overcome informality and the tax evasion associated with it. The work methodology is qualitative, with a documentary design and bibliographic review techniques. Literature and some local studies carried out in the country highlight a negative effect of informality on tax collection. However, national statistics show that the increase in informal work in the second decade of the 21st century was not accompanied by a decrease in said collection. This could be explained by the application of the Simplified Ecuadorian Tax Regime, which favored the payment of contributions by agents of the informal economy. It is concluded that training should be offered on this type of mechanism to reduce the impact of informality on taxation. It is also important to apply innovative formalization strategies to avoid unfavorable effects of informal work.
Keywords: informal economy; informal employment; tax collection; tax evasion